Conhecer, agir e sentir: a prática docente a partir da experiência estética - Santos, Maurício Inácio dos (2018)
This dissertation consisted of the analysis of the aesthetic experience in the teaching practice based on the contributions of the Critical Theory of the Society, specially of Theodor Adorno and Walter Benjamin. We sought to discuss the sense of experience and aesthetic experience as a possibility to reinvigorate the teaching work and recover its enchantment in the various teaching and learning situations in addition to the challenges that permeate the school routine. The problem that guided this research was to understand how aesthetic experience can support and nourish teaching practice in basic education in order to strengthen teaching work. The proposed objective for the theoretical discussion was the understanding of the aesthetic experience as an experience capable of enabling the entanglement between feeling, thinking and acting in the teaching practice, strengthening the pedagogical work of the teacher, based on the critical analysis of education in the context of the administered society and of its mechanisms that support domination, through the instrumental reason that imposes to all sectors of society and education, by extension to the teaching practice, a training centered on technical rationality and at the service of capital, to the detriment of an aesthetic experience capable of human formation in every way. It is a bibliographical and empirical research that had the technique of a questionnaire applied to teachers of basic education based on their diverse experiences, especially linked to teaching pedagogical practices. It was tried to observe and demonstrate that the school and the education have suffered a strong influence of the ideas and changes that marked the fields of culture, politics and economy throughout the time and that the instrumental reason, the cultural industry and the semicultura finished producing the reification and subjection of the individual. The uncritical consciousness, the submissive spirit, brutalized and fragile in its sensibility, has given rise to a damaged human bei ng and education, which in everyday school life is perceived in educational experiences reinforcing submission, acricity, lack of creativity and autonomy of the is often marked by the sadness, discouragement, dumbness of teachers, illusion and incarceration of educational practices that end up reproducing in the classroom the discourses of an education based on reason alone, aimed at the market of work, despising affection, sensitivity, emotion. It was observed a weakening of the sense of experience and aesthetic experience in the teaching practice from the moment that there is an impoverishment or negation of the question of the sensitivity in these practices, with emphasis more on the technical formation and the control of the discipline and not on a formation of the human being. Thus, it is defended the recovery of aesthetic experience in education as a way to strengthen the teaching work, from this practice as art and the teacher as a great craftsman of human formation. The teaching practice as art and the recovery of the sense of aesthetic experience, confers on the act of teaching and learning aesthetics that can strengthen the work of the teacher, although there are adversities, at the same time materializes the true and greater sense of education, the formation (Bildung) in every way.